Neighbour selection protocol for information dissemination through P2P interactions in opportunistic network - Abdalla Hassan, Gharib (Universiti Malaysia Sarawak, (UNIMAS), 2013)
he absence of network topology knowledge in Opportunistic Network makes information dissemination the most compelling research issue. Communication routes evolve when information is forwarded from source to destination during node interactions. The communications between nodes in Opportunistic Networks are supported through mobility of mobiJe nodes. The connections between mobile nodes are often disconnected. However, information can still be disseminated through the opportunistic connections which are computed dynamically Ideally, in Opportunistic Network when two nodes are in communication range, they should pair-wise identify each other. This process potentially facilitates the formulation of social relationship between those two nodes which later can be used to identify the best possible forwarder to deliver the information. However, formulation of the social relationship between neighbouring nodes and selection of the appropriate node to forward information in Opportunistic Network are not trivial processes. Flooding is the best technique to disseminate the information in Opportunistic Network, because it achieves high delivery ratios, minimize message latency and does not require any pre-existing network infrastructure. However flooding approach suffers from high message overhead due to forwarding the information to all nodes. . Considering the advantage of high delivery ratios of flooding, we proposed and designed the social based Neighbour Selection Protocol (NSP). The NSP uses Frequency in Range (FIR) and Frequency of Interaction (FOI) to assist the selection process. Each selected node in turn uses NSP to select a neighbouring node in order to disseminate information towards the destination. From the experimental results, we found that NSP can reduce the overhead and has delivery ratios close to flooding technique.